2012
DOI: 10.1088/0004-637x/761/2/161
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Contributions to the Stellar Halo From Accreted, Kicked-Out, and in Situ Populations

Abstract: We present a medium-resolution spectroscopic survey of late-type giant stars at mid-Galactic latitudes of (30 • < |b| <60 • ), designed to probe the properties of this population to distances of ∼9 kpc. Because M giants are generally metal-rich and we have limited contamination from thin disk stars by the latitude selection, most of the stars in the survey are expected to be members of the thick disk (<[Fe/H]>∼-0.6) with some contribution from the metal-rich component of the nearby halo.Here we report first re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 97 publications
5
65
0
Order By: Relevance
“…Acknowledging the much smaller net samples, we still find that even the more metal-rich stars of the LMg exhibit halo-like motions, which further justifies that the LMg population is a coherent and distinct population from the dynamically colder HMg population. (Nissen & Schuster 2010Navarro et al 2011;Ramírez et al 2012;Schuster et al 2012;Sheffield et al 2012;Jackson-Jones et al 2014;Hawkins et al 2015). These groups appear generally to correspond well with our HMg and LMg populations, as we now demonstrate.…”
Section: Kinematical Nature Of the Lmg And Hmg Populationssupporting
confidence: 90%
See 2 more Smart Citations
“…Acknowledging the much smaller net samples, we still find that even the more metal-rich stars of the LMg exhibit halo-like motions, which further justifies that the LMg population is a coherent and distinct population from the dynamically colder HMg population. (Nissen & Schuster 2010Navarro et al 2011;Ramírez et al 2012;Schuster et al 2012;Sheffield et al 2012;Jackson-Jones et al 2014;Hawkins et al 2015). These groups appear generally to correspond well with our HMg and LMg populations, as we now demonstrate.…”
Section: Kinematical Nature Of the Lmg And Hmg Populationssupporting
confidence: 90%
“…From the α-element abundances and kinematics of the two populations, these past studies have suggested that the low-α population has been accreted through the mergers of dwarf spheroidal-like galaxies (an origin also suggested for "young halo" globular clusters; see Zinn 1993), whereas the high-α stars were likely formed in situ or have been kicked out from the disk (Sheffield et al 2012;Johnston 2016). Recent studies have also revealed low-α bulge stars, most of which are thought to be chemically associated with the thin disk (Recio-Blanco et al 2017).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are due to the fact that in situ stars form in a deeper potential well than the accreted population. Several studies have used abundances in an effort to disentangle these populations locally (e.g., Nissen & Schuster (2010), with F and G main sequence stars within 335 pc; Sheffield et al (2012) with M Giants out to 10 kpc). However, no such studies exist using main sequence stars outside the solar neighborhood.…”
Section: Chemistrymentioning
confidence: 99%
“…accreted stars). These two populations are commonly referred as "α-rich" and "α-poor" (Nissen & Schuster 2010), which have been subject of interest among other studies (Ramírez, Meléndez & Chanamé 2012;Sheffield et al 2012). These two populations have been extensively studied in a series of papers by Schuster & Nissen. They have used a sample of high resolution and high signal-to-noise ratio (SNR) spectra of halo stars to show that these two populations are distinct in kinematics and abundances of α-elements (N10), but indistinguishable from other chemical abundances such as Li and Mn (Nissen & Schuster 2011.…”
Section: Introductionmentioning
confidence: 99%